COMPARATIVE TECHNO-ECONOMIC AND CARBON EMISSIONS ASSASEMENT OF BIOETHANOL AND BIOGAS PRODUCTION FROM Spirogyra sp. : A PROCESS SIMULATION STUDY. - Maharani, Nur Sista; Nugroho, Wahyunanto Agung; Wibisono, Yusuf (Jurnal Teknologi Pertanian, 2026)
The production of renewable energy from microalgal biomass offers a promising pathway to mitigate greenhouse gas emissions. This study compares the technical performance, economic feasibility, and carbon emissions of bioethanol and biogas production from Spirogyra sp. using SuperPro Designer 10.7. The results show that the technical performance is highly dependent on process configurations. The best-performing bioethanol scenario (E3-2: flotation–continuous fermentation) produced 537.37 kg/batch with an energy consumption of 41.81 MJ/kg . In comparison, the optimal biogas scenario (B1-1: mesophilic digestion–water scrubbing) yielded 1,026.56 kg/batch with a lower energy consumption of 7,614 MJ/kg . Techno-economic analysis revealed that all scenarios are currently economically unviable at the simulated scale due to negative Net Present Values (NPV < 0), despite some scenarios exhibiting positive Return on Investment (ROI). Biogas production demonstrated higher energy efficiency, while bioethanol offered a cleaner emission profile. An integrated biorefinery approach is recommended to improve overall economic viability and biomass conversion efficiency.